Physical Characteristics of Skin Powder, Chitin and Chitosan (Holothuria scabra) - Tyarani Dehwie; Sumarto Sumarto; Dahlia Dahlia (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study aims to determine the physical characteristics of skin powder, chitin and chitosan that prepared from skin of sea cucumber (H. scabra). The analysis parameters observed were physical characteristics, moisture content and ash content. The skin of H. scabra has blackish gray color with yellow and black spots originating from the dorsal part and white skin with yellow and brown spots originating from the ventral part. The color of skin powder was light gray. The color of chitin and chitosan were light cream. Moisture content of skin, skin powder, chitin and chitosan were 24.30%, 5.17%, 3.16% and 3.35% respectively. Ash content of skin, skin powder, chitin and chitosan were 62.92%, 61.10%, 3.05% and 1.42% respectively.